Metformin Improves Biochemical and Pathophysiological Changes in Hepatocellular Carcinoma with Pre-Existed Diabetes Mellitus Rats - Maysa A. Mobasher; Mousa O. Germoush; Hala Galal El-Tantawi; Karim Samy El-Said (Pathogens, 2021)
Hepatocellular carcinoma (HCC) is one of the world’s most widely recognized malignant tumors that accounts for 90% of all the primary liver cancers and is a major cause of death from cancer, representing half a million deaths per year. Obesity and associated metabolic irregularities, particularly diabetes mellitus (DM) and insulin resistance, are important risk factors for the advancement of HCC. Recently, retrospective studies showed that metformin (MET) could protect the hepatic tissues in pre-existing diabetes mellitus from HCC. The purpose of this study was to assess the role of MET treatment in the pre-existing diabetic rats before and after HCC induction by diethylnitrosamine (DEN). Thirty-five male Sprague Dawley albino rats were partitioned into the following groups: Group 1 (Gp1) was the control. Gp2 was injected intraperitoneally (i.p) with streptozotocin (STZ) (80 mg/kg) and DEN (50 mg/kg/7 weeks). Gp3, Gp4, and Gp5 were injected as in Gp2 and treated with MET (150 mg/kg) before and/or after HCC induction. Biochemical parameters including liver functions, lipid profile, and oxidative stress biomarkers were determined. Furthermore, histological and immunohistochemical changes were assessed in all groups. Our results illustrated that the group of rats that were treated with STZ and DEN had significant changes in both liver functions and were associated with alterations in the liver histopathological architectures. Treatment with MET before or after HCC induction ameliorated the cellular changes in the liver tissues; however, the utmost protection was found in a group of rats, which were treated with MET before and after HCC induction.